Nod2 regulates the host response towards microflora by modulating T cell function and epithelial permeability in mouse Peyer's patches. Issue 2 (15th October 2009) - Barreau, Frédérick; Madre, Chrystèle; Meinzer, Ulrich; Berrebi, Dominique; Dussaillant, Monique; Merlin, Françoise; Eckmann, Lars; Karin, Mickael; Sterkers, Ghislaine; Bonacorsi, Stéphane; Lesuffleur, Thécla; Hugot, Jean-Pierre
Abstract : Nucleotide oligomerisation domain 2 ( NOD2 ) mutations are associated with susceptibility to Crohn's disease and graft-versus-host disease, two human disorders related with dysfunctions of Peyer's patches (PPs). In Nod2 −/− mice transcellular permeability and bacterial translocation are increased in PPs. In this study, we show that both anti-CD4 + and anti-interferon γ (anti-IFN γ ) monoclonal antibodies abrogate this phenotype and reduce the expression of tumour necrosis factor (TNF) receptor 2 and the long isoform of myosin light chain kinase, thus demonstrating that immune T cells influence the epithelial functions. In turn, intraperitoneal injection of ML-7 (a myosin light chain kinase inhibitor) normalises the values of CD4 + T cells, IFN γ and TNF α . This reciprocal cross-talk is under the control of the gut microflora as shown by the normalisation of all parameters after antibiotic treatment. Toll-like receptor 2 (TLR2) and TLR4 expression were increased in Nod2 −/− mice under basal conditions and TLR2 and TLR4 agonists induced an increased transcellular permeability in Nod2 +/+ mice. Muramyldipeptide (a Nod2 agonist) or ML-7 was able to reverse this phenomenon. It thus appears that Nod2 modulates the cross-talk between CD4 + T cells and the epithelium recovering PP and that it downregulates the pro-inflammatory effect driven by the ileal microflora, likely by inhibiting the TLR pathways.